STUDI KOMPARASI KEKERASAN DALAM RUMAH TANGGA PERSPEKTIF ISLAM, PERSPEKTIF HAK ASASI MANUSIA DAN PERSPEKTIF HUKUM POSITIF INDONESIA (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2019)
Marriage is couple human beings who pledge to become couple lovers in accordance with Syari’at law and also the constitution. Despite that, the purpose of marriage is to build a harmonious household in order to provide descents who can be the successors of the ideals of the nation, religion and family. To deal with this, not all marriages can achieve that goal but there are various obstacles in the midst of the trip including the lack of harmony in the household so that domestic violence physical, psychological, sexual and family including the economy appeared. Violence is an inhuman and unlawful act creating a legal impact that must be accounted both in religious law, human rights and also positive Indonesian law. By this token, this study attempts to describe the comparison of domestic violence from three perspectives namely; Islamic perspective, human rights and positive Indonesian law. Thus, the researcher is able to know from the three laws that existed. To elaborate the specific design, normative research applied in this study. In addition, normative research is research used library materials or arguably also a library research or sources coming from scientific papers, articles, journals, laws, Al-Qur'an, Hadith, opinions of legal experts and also the opinions of fiqh or legal experts competent Islam as the research materials. Keyword : Violence, KDRT, UUPKDT, Islamic Law, Human Right, Positive Law Indonesia